2018
DOI: 10.1016/j.respol.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

How does openness influence the impact of a scholar’s research? An analysis of business scholars’ citations over their careers

Abstract: This is a repository copy of How does openness influence the impact of a scholar's research? An analysis of business scholars' citations over their careers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 92 publications
1
19
0
Order By: Relevance
“…6,10,20,23,28,30,33 Modifiable individual traits that support team science include positive attitudes toward collaboration 26,28 and cognitive openness, which includes a willingness to learn about the approaches of other disciplines. 23,34 In addition to several of the competencies listed above, including communication and management skills, Verdarme and colleagues 33 recommend that mentors or program sponsors assess specific skills and knowledge of early career scientists in order to evaluate their preparedness for interdisciplinary collaborations, including deep knowledge of one's own field, critical thinking skills, computational skills, and the ability to conduct sound research in an ethical, responsible, and reproducible manner.…”
Section: Team Science Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…6,10,20,23,28,30,33 Modifiable individual traits that support team science include positive attitudes toward collaboration 26,28 and cognitive openness, which includes a willingness to learn about the approaches of other disciplines. 23,34 In addition to several of the competencies listed above, including communication and management skills, Verdarme and colleagues 33 recommend that mentors or program sponsors assess specific skills and knowledge of early career scientists in order to evaluate their preparedness for interdisciplinary collaborations, including deep knowledge of one's own field, critical thinking skills, computational skills, and the ability to conduct sound research in an ethical, responsible, and reproducible manner.…”
Section: Team Science Competenciesmentioning
confidence: 99%
“…These include knowledge about best practices in interdisciplinary research [26][27][28], communication skills [3,6,10,20,22,23,26,[29][30][31][32][33], interpersonal relationship development and maintenance [3,6,20,29,30], meeting management and task coordination [20,30,32], goal setting [4,20,28,32], conflict management [6,32], and leadership skills [6,10,20,23,28,30,33]. Modifiable individual traits that support team science include positive attitudes toward collaboration [26,28] and cognitive openness, which includes a willingness to learn about the approaches of other disciplines [23,34]. In addition to several of the competencies listed above, Verdarme and colleagues [33] recommend that mentors or program sponsors assess specific skills and knowledge of early career scientists in order to evaluate their preparedness for interdisciplinary collaborations, including deep knowledge of one's own field, critical thinking skills, computational skills, and the ability to conduct sound research in an ethical, responsible, and reproducible manner.…”
Section: Team Science Competenciesmentioning
confidence: 99%
“…It is well known that scientific research topics in any subject field do not appear out of thin air, many of which are nurtured on the basis of past knowledge. Studies have shown that the research collaboration can provide the coauthors with higher research productivity [12], [13] and far-reaching research impact [14], [15], because it increases the number of available communication channels [16], [17], knowledge is better transferred and combined through collaboration. Therefore, with the increasing number of cooperation among researchers in different disciplines, it is possible to change the research topic or study multiple topics [18].…”
Section: A Related Workmentioning
confidence: 99%
“…Longstanding debates have considered the costs of engaging in Mode 1 knowledge creation (a single-discipline research focus) at the expense of Mode 2 (research that adopts multidisciplinary frameworks, particularly when seeking to tackle societally important research problems) (Gibbons, Limoges, Nowotny, Schwartzman, Scott and Trow 2002). Recent work in this area includes an analysis of the influence of multidisciplinary work (cognitive openness) and higher numbers of collaborations (structural openness) on the citation counts of individual researchers (Belkhouja and Yoon, 2018). This concern with the gap between research and practice is also echoed in another study that stresses the importance of management regimes in steering research toward Mode 1 outcomes at the expense of those of Mode 2 (Amara, Olmos-Peñuela and Fernández-de-Lucio, 2019).…”
Section: Theme 2: Silo-based Versus Multidisciplinary Research: Implications For Societal Contributionsmentioning
confidence: 99%